2021
DOI: 10.14393/bj-v37n0a2021-53576
|View full text |Cite
|
Sign up to set email alerts
|

Performance of brazilian university handball players in the vertical jump after maximum strength training

Abstract: This study aimed to analyze the performance of the vertical jump with counter movement (CMJ), in university handball athletes, immediately after the maximum strength training in multiple series and after 10 and 15min of rest. Twelve male athletes participated, age 20.9±2.4 years old, height 1.78±0.05m and Body Mass Index (BMI) 28.74±8.1kg/m2. After the tests and retests of 1 repetition maximum (1RM) for the dominant and non-dominant sides, in the leg extension, the volunteers performed crossover after 48 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…After the removal of duplicate articles, 2484 studies remained for the title and abstract screening. After full‐text screening of 286 articles, 51 articles 14,36–85 were ultimately included in the present scoping review. The rationale for exclusion at the full‐text level can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the removal of duplicate articles, 2484 studies remained for the title and abstract screening. After full‐text screening of 286 articles, 51 articles 14,36–85 were ultimately included in the present scoping review. The rationale for exclusion at the full‐text level can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In this context and in accordance with previous findings, 90 a higher RPE, which often implies greater fatigue in athletes, was found to relate to reduced jump performance as quantified by kinetic and kinematic variables, 52,55,78,84 and impaired postural control (Cohen's d ± 90% confidence limit = 0.68 ± 0.66; 6.9 ± 6.7%). 75 Specific to our focus on asymmetry however, we found that increased RPE was associated with reduced musculoskeletal strength of the nondominant limb compared to the dominant limb (i.e., increased between-limb differences) (r = 0.70, and r = 0.63-0.70, p < 0.05; and Cohen's d = 0.27-0.51, p < 0.05, respectively), 40,42 and greater kinetic or kinematic between-limb differences during vertical jump tasks (η p 2 = 0.24-0.53, p < 0.05; no effect size reported in Webster et al, 2012). 52,78 However, contradicting findings remain, 64 and the heterogeneous findings related to fatigue and lower limb asymmetry are often reported [91][92][93][94] due to the many nuances that exist in study designs, protocols, metrics assessed, and the calculation of asymmetries.…”
Section: Rate Of Perceived Exertion and Biomechanical Asymmetriesmentioning
confidence: 92%